Comparative Assessment of the Competitiveness of Private and Public Companies in the Russian Federation - VORONOV, Dmitrii Sergeevich; ERYPALOV, Sergei Evgenievich; PRIDVIZHKIN, Stanislav Viktorovich; KOZHEVNIKOVA, Margarita Karpovna; RUSETSKAYA, Elvira Antsasovna (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).36, 2018)
The competitiveness of the largest companies in the Russian Federation is analyzed in the study in order to assess the economic performance ratio of public and private companies. The article provides the justification of the fact that the most relevant method of assessing the competitive status of multiple economic entities is the dynamic method of assessing competitiveness, and its basic principles and mathematical apparatus are outlined. It has been shown that in the current Russian context private companies are not always more competitive as the public ones, which leads to the conclusion that premature privatization of state assets may lead to a reduction of the domestic national product and a decrease in the competitiveness of Russian assets on the international arena.